2021
DOI: 10.1136/bmjopen-2020-043547
|View full text |Cite
|
Sign up to set email alerts
|

Association of socioeconomic status with medical assistance in dying: a case–control analysis

Abstract: ObjectivesEconomic constraints are a common explanation of why patients with low socioeconomic status tend to experience less access to medical care. We tested whether the decreased care extends to medical assistance in dying in a healthcare system with no direct economic constraints.DesignPopulation-based case–control study of adults who died.SettingOntario, Canada, between 1 June 2016 and 1 June 2019.PatientsPatients receiving palliative care under universal insurance with no user fees.ExposurePatient’s soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…[38][39][40] Furthermore, our study demonstrated a lower OR for euthanasia and palliative sedation in the low-income group compared with middle and high-income groups, an association described in previous research. 38,41,42 These patients with a lower SES may feel less empowered and have lower health literacy, potentially leading to reduced self-advocacy and diminished trust in the health care system. [43][44][45] Additionally, it is plausible that despite clinicians' intentions to understand patient preferences, there might be less connection between lowincome patients and their health care clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Furthermore, our study demonstrated a lower OR for euthanasia and palliative sedation in the low-income group compared with middle and high-income groups, an association described in previous research. 38,41,42 These patients with a lower SES may feel less empowered and have lower health literacy, potentially leading to reduced self-advocacy and diminished trust in the health care system. [43][44][45] Additionally, it is plausible that despite clinicians' intentions to understand patient preferences, there might be less connection between lowincome patients and their health care clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…However, most people who utilize assisted dying services are likely to be financially stable, 41 and as such, these costs are not expected to impede MAiD access. Future research about the sociodemographic characteristics of MAiD-seeking individuals may reveal whether indirect cost burdens affect vulnerable groups differently.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Palliative care providers from Canada suggest that these concerns are valid, reporting significant challenges in providing palliative care after MAiD legalisation with moral ambiguity and provider distress, interprofessional team conflict and a negative impact on the perceived role of palliative care from the public and media [ 22 ]. Conversely, a recent paper from Victoria [ 23 ] argues that there may be “too much safety” with an over-emphasis on safeguarding coming at the expense of equity of access, which is already known to be less for those living rurally [ 18 ] and those of lower socioeconomic status [ 24 ].…”
Section: Discussionmentioning
confidence: 99%